Effect of Microwave Heat Processing on Nutritional Indices, Antinutrients, and Sensory Attributes of Potato Powder-Supplemented Flatbread. (15th February 2022) - Waseem, Muhammad; Akhtar, Saeed; Ahmad, Nazir; Ismail, Tariq; Lazarte, Claudia E.; Hussain, Majid; Manzoor, Muhammad Faisal
Abstract : This study aims at evaluating nutritional, toxicological, and sensory attributes of microwave heat-treated potato powder-supplemented unleavened flatbread. Straight-grade wheat flour (SGF) was substituted with potato powder at the rate of 2.5–10% d.w. A comparison was made for nutritional, antinutrient, and organoleptic attributes of microwave heat-treated potato powder and SGF—potato powder composite flour-based flatbreads. The results suggest processed potato powder supplementation in SGF to significantly (p < 0.05 ) improve ash (0.48 to 0.63 g/100 g), dietary fiber (2.15 to 2.61 g/100 g), and protein (8.33 to 9.91 g/100 g) contents of composite chapatis. Likewise, significant (p < 0.05 ) improvement in the concentration of microelements and trace elements was observed including Ca, Na, K, Fe, and Zn contents, which were increased from 29.7 to 33.5 mg/100 g, 2.8 to 6.3 mg/100 g, 376 to 466 mg/100 g, 3.1 to 3.4 mg/100 g, and 3.17 to 3.25 mg/100 g, respectively. Microwave heating of potato powder was observed to reduce the load of alkaloids, oxalates, tannins, and phytates of the raw potato powder at the rate of 76%, 80%, 84%, and 82%, respectively, thus anticipating a promising response to minimize toxicant load in supplemented flatbread. Supplementing potato powder in SGF elucidated significant (p < 0.05 ) improvement in color values, i.e., a ∗ (1.89–2.32) and b ∗ (10.95–13.22), and increased product hardness from 3.17 to 7.9 N. The study concludes that microwave heat-treated potato powder yield improved nutritional and safety concerns of the consumers when used alone or as a supplement for developing composite flours based on value-added products.